PENGEMBANGAN BAHAN AJAR MENGGUNAKAN GOOGLE SITES PADA MATA PELAJARAN PAI MATERI GERAKAN DAN BACAAN SHALAT - Yafie Al-Muhlasin; Lau Han Sein (Istifkar: Media Transformasi Pendidikan, 2023)
One of the innovations of learning media in the digital era is website-based learning media, one of which is the Google site. The purpose of this study was to determine the development of PAI movement teaching materials and prayer reading materials using Google Sites. This research is a type of research and development (research and development). The development model used in this research is the Borg and Gall model. The data analysis technique used descriptive quantitative. The results of this study indicate that the quality of teaching materials on motion material and prayer readings can be classified as very suitable criteria for teaching materials. This criterion is proven based on the results of the validation assessment by material experts who rate it with a percentage of 97%. Meanwhile, media experts gave an assessment that the use of Google Sites media in teaching materials for reading motion and prayer with an assessment result of 74.25%. The development of teaching materials for reading motion and prayer using Google Sites can function optimally and be effectively used in learning.